Implementing treatment guidelines for ambulance services in a low- and middle income setting. (13th November 2019) - Carlsson, H; Blaku, V; Lidberg, H; Hodza-Beganovic, R; Berggren, P
Abstract: Background: The use of clinical practice guidelines in clinical and organizational decision-making improves the care of patients and patient safety. Guidelines make healthcare consistent and efficient. In many low- and middle income countries healthcare workers depend on guidelines developed in higher income countries. For these to be useful and accepted they need to be adapted to the local setting. The aim of the study was to implement pre-hospital treatment guidelines into an organization that was not currently using guidelines. The study was partnership between a Swedish pre-hospital training organization and local ambulance service organizations in Kosovo. Methods: An iterative process of implementing the guidelines was used: Identify guidelines appropriate for the local organization. In sets of five, have the guidelines translated into Albanian. Adapt the guidelines to the local conditions and context. Approval of guidelines by an expert group. Begin using the guidelines within the target organization. Results: The first set of five guidelines was translated, approved, and implemented into the organizations. To improve acceptance, both practitioners and decision-makers were involved in the process. Seven workshops were held, with a total of 104 participants. In follow-up discussions participants said they accepted the guidelines and that they would be useful in their daily work. Conclusions: It is important to evaluate to what extent the guidelines have been accepted, understood, and used. The success and acceptance is due to the flexible procedure managing the full implementation process. Adapting guidelines to fit with local needs and requirements using local experts made the guidelines accessible and useful. The workshop discussions established justification and approval. Key messages: Involve local experts in contextualising guidelines to increase acceptance from the start. Support building a robust local implementation organization to assist and administer change.